An overview of consumer preferences for souvenirs in China post-COVID - Jin, Xiaolin; Sahari, Faridah; Azahar Shaik Hussain, Shaik (Edelweiss Applied Science and Technology, 2024)
The COVID-19 epidemic had a major effect on the travel sector worldwide, with China's souvenir market being especially hard hit. Examining post-COVID-19 tourist preferences for memento designs, this study also attempts to explore the ramifications for the souvenir design business as the tourism sector starts to recover. In order to find pertinent publications from 2019 to June 2024, a systematic literature review procedure based on the PRISMA criteria was used to scan the Web of Science and Scopus databases. After screening the collected literature for research themes and post-pandemic development trends, the VOSviewer tool was used to perform keyword co-occurrence analysis. Four primary research issues were established by the study: (1) the rationale for cultural tourism; (2) community involvement; (3) technological integration design; and (4) cultural economic analysis. It was discovered that travellers prefer personalised travel experiences and engaging with local culture, and that creating keepsakes using technology is becoming more and more popular. Travellers' tastes for Chinese souvenir designs have changed since COVID-19, and they are now more interested in individualised experiences, cultural components, and technological integration. The study's conclusions offer legislators, souvenir designers, and other tourism industry practitioners insightful information on how to promote innovation and long-term economic success.